Standard methods for marking caudate amphibians do not impair animal welfare over the short term: An experimental approach - David R Daversa; Ella Baxter; Gonçalo M Rosa; Chris Sergeant; Trenton WJ Garner (Animal Welfare)
Major advancements in ecology and biodiversity conservation have been made thanks to methods for marking and individually tracking animals. Marking animals is both widely used and controversial due to the potential consequences for animal welfare, which are often incompletely evaluated prior to implementation. Two outstanding knowledge gaps concerning the welfare consequences of individual marking are their short-term behavioural impacts and the relative impacts from marking versus the handling of animals while carrying out procedures. We addressed these knowledge gaps through an experimental study of alpine newts (Ichthyosaura alpestris) in which we varied handling and marking procedures. Examining individual responses to handling, toe clipping and visible implant elastomer (VIE) injection over 21 days showed that handling and marking elicited increased newt activity and hesitancy to feed compared to animals that did not get handled or marked. These effects were apparent even when animals were handled only (not marked), and marking did not further increase the magnitude of responses. Increases in newt activity and feeding hesitancy were transient; they were not observed in the weeks following handling and marking. While previous studies emphasise the welfare impacts of marking procedures themselves, these findings highlight that handling alone can elicit behavioural changes with possible costs to welfare. Yet, the transient nature of behavioural responses suggests that immediate costs of handling may be subsequently compensated for in the short term.